(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
The paper presents part of a comprehensive and complex investigation in the field of computer design and 3D garment simulation within which it investigates developed computer-based parametric prototype of a men's suit and whether it is suitable for computer adaptation according to measurements of different body characteristics. The investigation was conducted by segments. It was necessary to do tests and measurements using innovative computing technologies and appropriate measuring equipments. Using the 2D/3D CAD system for the preparation of garment construction, a 2D pattern was developed for the purpose of computer grading for selected sets of sizes according to different figures and statures. The scanning data process was performed through using a 3D laser scanner and a computer analysis was made with anthropometric measurements of the body on a sample of male subjects of different anthropometric body characteristics. The most complex part of the research was finding mathematical expressions and comprehensive development of a men's suit model with the aim of translating 2D pattern parts from vector into parametric format, which allows simultaneous changes in several corresponding segments of pattern pieces.